Busulfan-containing conditioning regimens are optimal preparative regimens for autologous stem cell transplant in patients with diffuse large B-cell lymphoma. Issue 11 (November 2014) - Shin, Ho-Jin; Lee, Won-Sik; Lee, Ho-Seop; Kim, Hawk; Lee, Gyeong-Won; Song, Moo-Kon; Kim, Jin Seok; Yhim, Ho-Young; Chung, Joo Seop
Abstract We retrospectively examined the outcomes of 56 patients with diffuse large B-cell lymphoma (DLBCL) who underwent autologous stem cell transplant (ASCT) with BEAM/BEAC (carmustine, etoposide, cytarabine, melphalan/cyclophosphamide) or busulfan (Bu)-containing conditioning regimens. The Bu group had lower disease-related mortality and more frequent achievement of complete remission (CR) after ASCT from partial remission (PR) or refractory status before ASCT compared with the BEAM/BEAC group. The estimated 2-year EFS (59.3% vs. 15.0%) and overall survival (OS) (70.2% vs. 42.0%) in pre-ASCT rituximab-exposed patients with DLBCL were higher in the Bu group. In patients with high-risk DLBCL exposed to rituximab with first remission, the Bu group had better EFS (p = 0.004) and OS (p = 0.053) rates, while survival rates for relapsed/refractory patients did not differ between groups. Bu regimens are highly effective for preparing patients with DLBCL with previous exposure to rituximab for ASCT, especially in high-risk patients who achieved a first remission.